Eksistensi Kontrak Lisan Dalam Hukum Komersial Indonesia:Tantangan Pembuktian Dalam Sengketa Bisnis - Khairani Alawiyah Matondang; Juanda Maulana; Tegar Efraim Gilbert Siahaan; Alawi Parlindungan Hasibuan (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the legal status of oral contracts in the Indonesian commercial legal system, identify the challenges of proving them in business disputes, and examine relevant dispute resolution mechanisms. The method used is normative legal research with a qualitative approach. Data were obtained through a literature review covering primary, secondary, and tertiary legal materials, such as laws and regulations, court decisions, books, and scientific journals related to oral contracts and the law of evidence. Data analysis was conducted descriptively and qualitatively through a statutory, conceptual, and case approach. The results show that oral contracts have valid and binding legal standing based on the principle of consensualism and the provisions of Article 1320 of the Civil Code. However, in dispute resolution practice, oral contracts face serious obstacles in the aspect of proof because they are not supported by strong written evidence. The presence of electronic evidence, such as digital messages and communication recordings, is an important alternative in strengthening evidence. Therefore, supporting documentation and regulatory updates are needed to increase legal certainty and protection for parties in business relationships.